Genetic association of ABCA7 and PSEN1 polymorphisms with Alzheimer’s disease in the northeast Algerian population: Exploring risk factors - Achou, Rayene; Ayachi, Ouarda Sariyah; Boukhenaf, Yasmina; Laouar, Rania; Gharzouli, Razika; Mzahem, Abderrahim; Boulala, Houda; Abadi, Noureddine; Satta, Dalila (Archives of Biological Sciences, 2025)
Paper description: ABCA7 and PSEN1 genes are implicated in Alzheimer's disease (AD) susceptibility due to their role in β-amyloid accumulation and neurodegeneration. Investigating these variants in the Algerian population allows for the assessment of their contribution to AD risk in a distinct genetic context. A case-control study examined the association of ABCA7 rs3764650 and PSEN1 rs165932 with AD risk using PCR-RFLP genotyping. A significant association was found between rs3764650 and rs165932 and AD, particularly in late-onset cases and females. This study enhances understanding of AD genetics in the Algerian population, emphasizing the need for targeted studies and potential genetic screening. Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder with a strong genetic component. This research aims to identify the relationship between ABCA7 rs3764650, PSEN1 rs165932, and AD in the northeast Algerian population and investigate genetic risk factors contributing to disease susceptibility. A case-control study was performed with 98 patients and 156 controls. DNA was isolated from blood samples by salting out. Genotyping of ABCA7 and PSEN1 polymorphisms was conducted using PCR-RFLP. Significant associations were observed between ABCA7 rs3764650 and AD under dominant and additive models. Similarly, PSEN1 rs165932 was associated with a higher risk of AD under dominant, recessive, and additive models. The frequency of the ABCA7 G allele was significantly associated with PSEN1 T allele carriers (P=0.033), with no significant association observed in non-carriers. In contrast, the PSEN1 T allele frequency was significant in both ABCA7 G allele carriers (P=0.006) and non-carriers (P=0.001). Allelic frequencies for ABCA7 and PSEN1 were higher in late-onset cases (P=0.003; P< 0.001) and females (P=0.006; P< 0.001). This study highlights the association of the ABCA7 rs3764650 G and PSEN1 rs165932 T alleles with AD susceptibility, particularly in females and late-onset cases, suggesting their relevance as genetic markers of disease risk.